2017
DOI: 10.1039/c7ra01598d
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of mesoporous titanosilicates for styrene oxidization using a nanocellulose template strategy

Abstract: A nanocellulose-template strategy is reported for the controllable synthesis of mesoporous titanosilicates as efficient catalysts for the oxidization of styrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…hydroxyl groups), making them ideal as templates in preparing composite materials, which is exemplified by the work on CNCs-templated mesoporous amorphous silicates. [21][22][23][24] Unlike the conventional carbon materials, CNCs are intrinsically compatible with zeolite synthesis protocols due to their reactive surfaces and hydrophilicity as a result of the hydroxyl groups on their crystalline facets. Previous research showed that, in the process of zeolite crystallisation, cellulose in the vegetal fibres is the reactive component, rather than lignin and pectin, which interacts with the aluminosilicate species, and hence promotes the formation of zeolite nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…hydroxyl groups), making them ideal as templates in preparing composite materials, which is exemplified by the work on CNCs-templated mesoporous amorphous silicates. [21][22][23][24] Unlike the conventional carbon materials, CNCs are intrinsically compatible with zeolite synthesis protocols due to their reactive surfaces and hydrophilicity as a result of the hydroxyl groups on their crystalline facets. Previous research showed that, in the process of zeolite crystallisation, cellulose in the vegetal fibres is the reactive component, rather than lignin and pectin, which interacts with the aluminosilicate species, and hence promotes the formation of zeolite nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption at 459 cm –1 is related to the silanol bending, and the vibration of asymmetric and symmetric stretching vibrations of Si–O–Si are assigned to the bands at 1084 and 801 cm –1 , respectively. These characteristics also indicated the retention of the original structure, meaning the prepared bifunctional catalysts can preserve the merits of the mesoporous silica supports. Meanwhile, a band at 969 cm –1 for the obtained samples could be explained as the framework Si–O–M vibrations, reflecting the incorporation of the metal species into the silica framework. , The band at 1647 cm –1 corresponded to the hydroxyl deformation mode on the material surface …”
Section: Resultsmentioning
confidence: 92%
“…Meanwhile, a band at 969 cm −1 for the obtained samples could be explained as the framework Si−O−M vibrations, reflecting the incorporation of the metal species into the silica framework. 42,43 The band at 1647 cm −1 corresponded to the hydroxyl deformation mode on the material surface. 44 The N 2 adsorption−desorption test and the detailed textural parameters of the prepared samples are displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Dazhi Shen et al [70] applied a nanocellulose template strategy to synthesize mesoporous titanosilicates for styrene epoxidation. Firstly, treated cotton with H 2 SO 4 to generate nanocellulose.…”
Section: Mofsmentioning
confidence: 99%